In vitro biochemical features of cold plasma application in MCF-7 experimental breast cancer cells - A. B. Zinnurova; K. P. Vorobyev; O. V. Bakina; E. I. Senkina; L. V. Spirina; O. L. Nosareva; T. V. Zhavoronok (Сибирский онкологический журнал)
Introduction. Low-temperature plasma is currently used in medicine, including cancer therapy. Plasma-activated biological solutions have already been proposed as potential reagents for cancer treatment. However, the biological effects in cells induced by exposure to cold plasma still remain unexplored. Investigation of the molecular mechanisms of the effects of cold plasma on cells is of great clinical importance for its clinical application. the aim of the present study was to evaluate the effect of cold plasma exposure on apoptosis, catalase activity, and malonic dialdehyde content in MCF-7 breast cancer cell cultures compared to 3T3 normal fibroblast cells. Material and Methods. MCF-7 mammary epithelial cells were used as research objects, and NIH/3T3 mouse embryonic fibroblast cells were used as controls. Cell suspensions were treated using low-temperature atmospheric discharge plasma with escaping electrons. Annexin V and propidium iodide were used to quantify cell line apoptosis. The content of malonic dialdehyde was determined by the developing coloration of its solution with 2-thiobarbituric acid at high temperature in acidic medium. The activity of catalase was estimated by the rate of decomposition of hydrogen peroxide for a certain time of incubation of the mixture. Results. It was found that irradiation of MCF-7 cell culture with plasma led to an increase in the content of malondialdehyde, the main product of lipid peroxidation. the increase in this parameter is an indicator of cell membrane damage and oxidative stress induced by irradiation. In addition, under the same irradiation regime, cold plasma showed a stimulating effect on the culture of 3T3 cells, while on the MCF-7 culture, on the contrary, it stimulated the activation of apoptosis and cell death. Conclusion. In the present study, we found that exposure of tumor and normal cells to cold plasma promotes apoptosis activation. Catalase and MDA activity have been shown to be significant markers capable of assessing the intensity of oxidative stress.